Systematic reviews and meta-analyses on major depressive disorder: a bibliometric perspective - Chen, Pan; Feng, Yuan; Li, Xiao-Hong; Li, Jia-Xin; Wang, Yue-Ying; Zheng, Wan-Ying; Su, Zhaohui; Cheung, Teris; Ungvari, Gabor S.; Ng, Chee H.; Sha, Sha; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background: There is a vast amount of evidence-based medicine research on the major depressive disorder (MDD) available in the literature, however, no studies on the overall performance, productivity and impact of such research have been published to date. This study explored and mapped the research outputs of MDD related systematic reviews and meta-analyses (SR/MA) from a bibliometric perspective. Methods: Relevant data were retrieved, with search terms on MDD, systematic review and meta-analysis. Results: A total of 4,870 papers with 365,402 citations published from 1983 to 2022 were included in the analysis. The publication trend has grown steadily over time with the most publications originating from The USA (1,020; 20.94%), the UK (516; 10.60%) and China (448; 9.20%). The research collaborations between countries were most frequent between the USA and UK (266; 5.46%). Journal of Affective Disorders (379; 7.78%) was the most productive journal, while Cuijpers P was the most productive author (121; 2.48%), and the University of Toronto (569; 11.78%) was the most productive institution. The top 10 most cited articles on MDD related SR/MA had citations ranging from 1,806 to 3,448. The high-frequency keywords were mainly clustered into four themes, including psychiatric comorbidities, clinical trials, treatments, and brain stimulation in MDD. Conclusion: The rapid increase in the number of SR/MA of MDD in recent years highlights the importance of this research field. Psychiatric comorbidities, clinical interventions, and treatments of MDD have been identified as hot topics, while biological mechanisms in MDD are likely to be an emerging future research priority.